On intersecting modes of responsibility in Australia and Aotearoa New Zealand: a case for reimagining responsible innovation - M. Espig; S. Provost; A. W. Russell; J. N. M. Viaña; C. Koroheke; S. Finlay-Smits (Journal of Responsible Innovation)
This Perspective considers the potential value and limitations of introducing Responsible Innovation approaches from the Global North into Australia and Aotearoa New Zealand. We reflect on the relationship of predominantly Western European understandings of responsibility and endogenous ‘Antipodean’ forms of responsibility, including Indigenous relationalities, collective stewardship, and care that extends to more-than-human worlds. Commencing a dialogue between these different modes of responsibility, we outline incommensurabilities, complementarities, and tensions within two core dimensions of Responsible Innovation, namely anticipation and inclusion. To realise benefits from introducing Responsible Innovation and avoid neo-colonial enforcements of adventitious understandings of responsibility, ‘Antipodean’ practitioners need to understand their multidimensional cultural contexts with the aim of collectively reconfiguring responsible practices. Pursuing intercultural dialogue with ‘Antipodean’ modes of responsibility can, in turn, help to responsibly innovate Responsible Innovation outside of the Global North and strengthen the concept’s foundational ethos of collective stewardship by making it more inclusive and multifaceted.